A retinoic acid receptor β agonist (CD2019) overcomes inhibition of axonal outgrowth via phosphoinositide 3-kinase signalling in the injured adult spinal cord - Agudo, Marta (Academic Press, 2010)
After spinal cord injury in the adult mammal, axons do not normally regrow and this commonly leads to paralysis. Retinoic acid (RA) can stimulate neurite outgrowth in vitro of both the embryonic central and peripheral nervous system, via activation of the retinoic acid receptor (RAR) β2. We show here that regions of the adult CNS, including the cerebellum and cerebral cortex, express RARβ2. We show that when cerebellar neurons are grown in the presence of myelin-associated glycoprotein (MAG) which inhibits neurite outgrowth, RARβ can be activated in a dose dependent manner by a RARβ agonist (CD2019) and neurite outgrowth can occur via phosphoinositide 3-kinase (PI3K) signalling. In a model of spinal cord injury CD2019 also acts through PI3K signalling to induce axonal outgrowth of descending corticospinal fibres and promote functional recovery. Our data suggest that RARβ agonists may be of therapeutic potential for human spinal cord injuries.